Exploring The Antibacterial Potential of Aqueous and Ethanol Extracts from Bawang Dayak (Eleutherine palmifolia (L.) Merr) Against Skin Infectious Bacteria Through KLT-Bioautography - Rusli, Rusli; Nuryanti, Siska; Putria, Yashifa Anandita (Journal Microbiology Science, 2024)
Dayak onion plants (Eleutherine palmifolia (L.) Merr) have chemical compounds that have potential as antibacterials such as alkaloids, glycosides, flavonoids, phenolics, steroids and tannins. This study aims to determine the antibacterial activity of water extracts and ethanol extracts of dayak onion bulbs (Eleutherine palmifolia (L.) Merr). This research was conducted with the stages of sample extraction, screening of test bacteria, bioautogram profile testing and antibacterial activity by KLT-Bioautography method. Screening test results at a concentration of 1% against test bacteria Propionibacterium acnes, Pseudomonas aeruginosa, Staphylococcus aureus and Staphylococcus epidermidis were able to inhibit the growth of test bacteria. Then continued with KLT-Bioautography testing using n-hexan: ethyl acetate (2: 1) eluent. The KLT-Bioautography test results showed that there was 1 active spot with an Rf value of 0.63 in the water extract and an Rf value of 0.60 in the ethanol extract against Pseudomonas aeruginosa, Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis bacteria. Based on the research, water extract and ethanol extract of dayak onion bulb (Eleutherine palmifolia (L.) Merr) have potential as antibacterial.Keywords: Antibacterial, KLT-Bioautography, Dayak Onion Bulbs